PENGEMBANGAN PROTOTIPE SMART WATER TANK BERBASIS INTERNET OF THINGS DENGAN SISTEM DUAL TANK DAN FILTRASI OTOMATIS UNTUK MONITORING ADAPTIF KETINGGIAN DAN KUALITAS AIR - Nayla Putri Iman; Masagus Rifky Rianggi; Prastya Wicaksana; Ismajuanti; Ratna Atika (Teknik Elektro Polsri, 2026)
The availability of sufficient and high-quality water is essential in daily life. However, monitoring water levels and water quality in storage tanks is still commonly performed manually, making the process less efficient and potentially causing delays in water refilling and the use of unsuitable water. The development of Internet of Things (IoT) technology enables water monitoring and control to be carried out automatically and in real time. This study aims to design and develop an IoT-based Smart Water Tank system using a dual-tank concept to monitor water levels and water quality automatically. The methods employed include system design, ESP32 programming, integration of water level and turbidity sensors, and system testing. The test results showed that at water volumes of 0–500 mL, the pump was activated to fill the tank. When turbid water was detected at 1000–1500 mL, the filtration system was activated automatically. At 2000 mL, the pump and filter stopped operating because the tank was full and the water was clear. Monitoring data could also be accessed in real time through Google Spreadsheet. The developed system integrates automatic water monitoring and management to improve the efficiency of water storage management.Key words : Smart Water Tank, Internet of Things, ESP32, Water Level Sensor, Turbidity Sensor.